2008
DOI: 10.1108/09564230810891941
|View full text |Cite
|
Sign up to set email alerts
|

The impact of other‐customer failure on service satisfaction

Abstract: Purpose -The purpose of this paper is to investigate how and why other-customer misbehavior has a negative influence on customer satisfaction with the service firm. Design/methodology/approach -Data for this study were gathered by retrospective experience sampling. Findings -There are several important findings that can be obtained from the results. First, people consider another customer's failure to be the firm's responsibility when they perceive that the failure is under the firm's volitional control (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 51 publications
(66 reference statements)
1
136
3
9
Order By: Relevance
“…Therefore, previous studies argued that service failure severity influences customers' satisfaction (Smith et al, 1999;Weun et al, 2004), assuming that failures classification is very important for firms (Kuo et al, 2011). Service failure severity is the customer's perceived intensity of a critical incident and there is a positive relationship between customers' perceived loss and failure severity (Weun et al, 2004;Huang, 2008): as failure severity increases, customers' perceived loss decreases. Service recovery expectations may vary positively with the failure severity (Bitner et al, 1990;Hoffman et al, 1995) and even after an adequately recovery, a severe failure (outcome or process) will produce a perceived loss (Weun et al, 2004).…”
Section: The Impact Of Service Failure Context On Customers' Behaviormentioning
confidence: 99%
“…Therefore, previous studies argued that service failure severity influences customers' satisfaction (Smith et al, 1999;Weun et al, 2004), assuming that failures classification is very important for firms (Kuo et al, 2011). Service failure severity is the customer's perceived intensity of a critical incident and there is a positive relationship between customers' perceived loss and failure severity (Weun et al, 2004;Huang, 2008): as failure severity increases, customers' perceived loss decreases. Service recovery expectations may vary positively with the failure severity (Bitner et al, 1990;Hoffman et al, 1995) and even after an adequately recovery, a severe failure (outcome or process) will produce a perceived loss (Weun et al, 2004).…”
Section: The Impact Of Service Failure Context On Customers' Behaviormentioning
confidence: 99%
“…Bir başka çalışmada, yakın sosyal ilişkilerin söz konusu olduğu kuaför salonlarını inceleyen Moore, Moore ve Capella (2005), müşteri sadakati ve tavsiye etme davranışı üzerinde rol oynayan müş-terilerarası ilişkilerin atmosferden etkilendiğini göstermiştir. Huang (2008) Kuzey Tayvan'daki bir alışveriş merkezinde gerçekleştirdiği çalışma-da, katılımcıların alışveriş deneyimleri üzerinde başka müşterilerden kaynaklanan olumsuz olayların etkisini araştırmıştır. Elde ettiği sonuçlar müşterilerin hizmet değerlendirmelerinin sadece diğer müşterilerin olumsuz davranışlarından etkilenmediğini, aynı zamanda bu tür davranışlar karşısında işletme personelinin gösterdiği reaksiyonun da müşteriler açısından önem taşıdığını yansıtmıştır.…”
Section: Müşterilerarası Etkileşimlerunclassified
“…Ancak mevcut alanyazında müşteri-personel etkileşimlerini ele alan çok sayıdaki çalışmaya karşılık, müşterilerarası etkileşimleri inceleyen çalışmaların sayısı sınırlıdır (Zhang, Beatty ve Mothersbaugh 2010;Yoo, Arnold ve Frankwick 2012). Mevcut araştırma sonuçları ise müşterile-rin diğer müşterilerle olan olumlu ve olumsuz etkileşimlerinin hizmet işletmesine yönelik değerlendirmeleri (Mourali 2003;Miao ve Mattila 2013), memnuniyeti (Wu 2007;Huang 2008) ve tekrar gelme/satın alma niyetini (Martin ve Pranter 1989) doğrudan etkilediğini göstermek-tedir. Bu açıdan Palmer'ın da (2005) belirttiği gibi müşterilerarası etkileşimleri anlayabilmek; diğer müşterileri olumlu veya olumsuz şekilde etkileyen müşterilerin başlıca niteliklerini belirleyebilmek önemlidir.…”
unclassified
“…Previous research has indicated that misbehaviours from jaycustomers have negative effects on customers' overall perceptions and evaluations of their experiences in a service environment (Harris and Reynolds, 2003). Moreover, Huang (2008) suggested that dysfunctional behaviours from other patrons may affect customer behaviour, but this supposition requires further research. Accordingly, we examined the relationships among the physical environment, emotional responses of customers, misbehaviours of jaycustomer, and the relative behavioural intentions in themed restaurants.…”
Section: Introductionmentioning
confidence: 99%